A 1, 2, 3-triazole-derived pincer-type mesoionic carbene complex of iron(ii): carbonyl elimination and hydrosilylation of aromatic aldehydes via the concerted reaction with hydrosilane and a base. Issue 3 (20th December 2022) - Matsubara, Kouki; Yamada, Yuji; Iwasaki, Haruka; Ikeda, Hayao; Kanetsugu, Yuki; Kawata, Satoshi; Koga, Yuji
Abstract : The CO ligands of dicarbonyl Fe(ii ) complex thermally liberated with a spin-state change from singlet to quintet. Hydrosilylation of aromatic ketones and aldehydes occurred, via concerted transmetallation with base and silane, based on calculations. Abstract : Iron complexes bearing 1, 2, 3-triazol-5-ylidene were synthesized and applied to the reaction with hydrosilane and homogeneous catalytic hydrosilylation of aromatic ketones and aldehydes. Addition of a free carbene to a solution of Fe(CO)4 Br2 yielded an octahedral, diamagnetic and cationic iron(ii ) complex [Fe(1, 2, 3-triazolylidene)(CO)2 Br] + . Pyrolysis of the dicarbonyl complex eliminated the two CO ligands to form a paramagnetic four-coordinate complex. A theoretical study using DFT calculations indicated that the spin state changed from singlet to quintet during ligand elimination. Investigations of the successful hydrosilylation of acetophenone and benzaldehyde derivatives using MIC–iron(ii ) bromide suggested the importance of the base for efficient conversion in the catalytic process. The bromide-to-hydride exchange reaction, transmetallation, of MIC–iron(ii ) bromide in the presence of KO t Bu and HSi(OEt)3 which could occur in the initial process of hydrosilylation was proposed, and supported by a theoretical study.